(In)vulnerable managers in an immigration context - Kivijärvi, Marke (Journal of business ethics, 2024)
Our study examines managerial vulnerability in a bureaucratic context, namely in Finnish immigration centres. We bring a care ethics perspective to the study of vulnerability and address how managers navigate relationships with vulnerable clients and their own vulnerability. Based on empirical data collected through interviews with immigration centre managers, we show how managers negotiated their (in)vulnerability through two alternating positionalities: (1) professionalism, through which they seek to control negative emotions in order to manage their own experiences of vulnerability and affective relationships with clients, and (2) temporal disconformity, which provides space to engage and manage with a variety of emotions and manoeuvre bureaucratic professional norms. Our study then contributes to the literature on managerial work by demonstrating how managers cope with their vulnerable selves and how different notions of care emerge in complex, ethically sensitive managerial situations.